Effect of Alltech® Crop Science products on root-knot nematode attraction and infestation in tomato plants - Anusha Pulavarty; Ross Daly; Karina Horgan; Thomais Kakouli-Duarte (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science, 2021)
Root-knot nematodes (RKN) are highly damaging pests with broad host range causing crop yield loss of about 30% in susceptible crop varieties annually. Natural-based products for RKN management have gained a lot of interest due to the harmful effects of conventional chemical nematicides. Two Alltech Crop Science products, (ACS5075 and ACS3048), were evaluated against the RKN Meloidogyne javanica. Attraction assays were performed by adding either product to 20% (w/v) Pluronic F-127 gel to study the behaviour of RKN second-stage juveniles (J2) towards host roots. ACS5075 completely inhibited attraction of RKN juveniles towards roots when compared to ACS3048 (7 ± 1 juveniles) or the control (8 ± 0.5 juveniles). Pot trials were also conducted for 2 months, where several combinations of products were assessed to determine their impact on egg masses and plant development. The ACS5075 treatment caused a significant reduction in egg masses (2.04 and 1.4 fold) when applied at 1% and 3% (p ≤ 0.05), respectively, compared to inoculated control. Correlation studies (r = −0.414) clearly depicted positive contribution of the product towards plant growth while reducing egg mass formation. A combination of 3% ACS5075 and 3 g ACS3048 behaved similarly. It is concluded that these products could potentially provide promising alternatives for sustainable RKN management.